О социально-стилевой девиации президентского дискурса - Koriakowcewa, Elena (Studia Rossica Posnaniensia, 2025)
The article studies the phenomenon of socio-stylistic deviation of the classical presidential discourse demonstrated in vulgarization and invectivization of the normative communication language of Russian Federation president on national and international levels of interaction. The author used linguopragmatic and sociolinguistic methods, as well as elements of content analysis, to investigate the presidential public discourse deviation. The invective function aimed at offence, humiliation and ridicule of the opponents by the speaker in partisan competition or in the opposition on the international level is realized by Vladimir Putin in the deviant usus of president’s discourse via switching over to a profane language employing the methods of political trolling, obscene words, invective paralinguistic means, etc. The purpose of conscious degradation of the institutional level of presidential discourse may be in an effort to attract the provincial voters to one’s side in a current presidential or parliamentary election campaign. However, our results of analysis show that the expressiveness of argotic lexemes in presidential discourse can cause negative associations and create images of similarities between political life and the actions of politicians and the world of crime.